ANALYSIS OF AN ALGERIAN- TYPOLOGY OF HOUSING (Sciences & Technologie. D, Sciences de la terre, 2012)
Algeria possesses a great architectural experience.In that sense, we can find a great diversity of traditional architectural model, which mainly varies according environmental and geographical factors (situation).  These very models are actually, the expression of local architecture realised with local building materials and techniques, reflecting thus, a restrained culture and way of life.